YOUTHS CONDITION IN THE LABOUR MARKET DURING THE POST-CRISIS PERIOD - Mariana BALAN (Hyperion Economic Journal, 2015)
Unemployment among youth in the EU had a strong increase from the outbreak of the financial crisis in 2008, and reached unprecedented levels. Nevertheless, for over a decade the youths’ unemployment rate remained approximately double against the global unemployment rate in time for the whole economy. In this context, the concept of NEET has been introduced to characterize the size and structure of a vulnerable group of young people i.e. those young people who are not engaged in any form of employment, education or training. The year 2014 registered a slight decrease of both unemployment rate and of the NEET rate among youths. According to the Eurostat statistics, in 2014, within the EU the average unemployment rate for youths with ages between 15 and 24 years diminished by 1.4 pp., and for the age group aged between 25 to 29 years, by 1 pp. Also the NEET rate for various young population segments registered in most member countries a decreasing trend. In Romania, the NEET population rate (youths between 15 and 29 years of age) under the impact of the economic financial crisis increased from 13.2% in the year 2008 to 19.6% in the year 2014. This paper intends to be a brief analysis of the youths’ condition in the EU countries’ labour markets from the beginning of the financial crisis by focusing mainly on describing the characteristics of youths that don’t have a job, and are not included in the educational or vocational training system (NEET). There are large differences between the youths and the employment in the member-states, and these differences were exacerbated by the recession.